COMPRESSIONAL SUBDUCTION REGIME AND INITIAL ARC-CONTINENT COLLISION: NUMERICAL MODELING - Tang J.-C.; Chemenda A.I.; Chéry J.; Lallemand S.; Hassani R. (My University, 2002)
We performed two-dimensional finite-element numerical modeling of subduction to study the deformation and failure pattern of an overriding plate. This plate has elasto-plastic rheology with strain weakening and contains a "volcanic arc" represented in the model as a thinned and rheologically weakened zone. The subducting plate is not modeled directly. Its effect on the overriding plate is simulated by the normal and tangential stresses along the interplate surface, which correspond to the interplate pressure and interplate friction, respectively. Both stresses cause nonhydrostatic (tectonic) compression on this plate. The first approximation for the interplate pressure is derived from previous experimental modeling of subduction of oceanic lithosphere. Numerical modeling shows that the overriding plate fails under the arc along a trenchward-dipping fault. We then vary both the interplate pressure and the interplate friction and show that the failure direction does not change. Subduction of the continental margin modifies (increases) the interplate pressure because of the buoyancy of thick continental crust. The compressive stress in the overriding plate increases. Failure of this plate can occur in the same way as indicated or in the opposite direction along a fault that dips under the arc (away from the trench and toward the ocean. The failure mode depends in particular on the depth of the margin's subduction prior to lithosphere rupture. Failure along a fault dipping toward the continent results in a subduction reversal, whereas failure along a fault dipping toward the ocean is followed by subduction of a forearc block beneath the arc. Both scenarios seem to have natural analogues.We consider one analogue, the ongoing arc-continent collision in Taiwan, and argue that this process occurs according to the second scenario, which involves forearc subduction.